Market Efficiency in the MENA Equity Markets: Evidence from Newly Developed Tests and Regime Change - Ata Assaf, Ata Assaf; Charif, Husni (Journal of Reviews on Global Economics, 2017)
A major issue in financial economics is the behavior of stock market returns over long horizons. This paper provides an empirical investigation of the random walk hypothesis in the MENA equity markets. We use the variance ratio tests developed by Wright (2000), Kim and Wang and Chow Denning (1993) to test for the weak form market efficiency. Then, we use the unit root tests proposed by Saikkonen and Lütkepohl (2002) and Lanne et al. (2002), which allow for a level shift in the data generating process. Our results confirm the stationarity of the MENA equity markets returns in the presence of structural breaks, with the breaks happening mostly during the 2008 and 2009 periods. Further, the findings from our sub-samples indicate that the results from the last sub-periods support the belief that these markets may have been approaching a state of being fairly weak-form efficient, which reflects the future prospects of the MENA countries.